Fundamental Astronomy - Karttunen, Hannu; Kröger, Pekka; Oja, Heikki; Poutanen, Markku; Donner, Karl Johan (Springer, 2017)
As the title suggests, this book is about fundamental things that one might expect to remain fairly the same. Yet astronomy has evolved enormously over the last few years, and only a few chapters of this book have been left unmodified. Since the book is used also by many amateurs, the introductory chapter has been extended to give a brief summary of different celestial objects to “soften” the jump to rather technical topics. The chapter on the solar system was very long. It has now been split into two separate chapters. Chapter 7 deals with general properties of the solar system. Individual objects are discussed in Chap. 8, which is more prone to change when new data will accumulate. Also, new data on exoplanets is obtained at an increasing rate. Therefore exoplanets are given a chapter of their own; it is at the end of the book, since it is closely related to astrobiology, already included in the previous edition. These last chapters may change more than the rest of the book in the future. These changes mean that the numbering of formulas and figures has changed quite extensively after the previous version of the book. Cosmology and galactic astronomy have still been evolving rapidly. Therefore there are many revisions to the chapters on the Milky Way, galaxies, and cosmology. In addition, several other chapters contain smaller revisions and many of the previous images have been replaced with newer ones.